Effects of Light-Emitting Diode Photobiomodulation Therapy and BioOss as Single and Combined Treatment in an Experimental Model of Bone Defect Healing in Rats - (:unkn) unknown (My University, 2015)
The present study assesses histopathologically and histomorphometrically the effects of light-emitting diode (LED) photobiomodulation therapy (LPT) on bone healing in BioOss-filled femoral defects of rats. It has been reported that LPT modulates cellular metabolic processes, leading to an enhanced regenerative potential for biological tissues. Thirty-six male Wistar rats with femoral bone defects were divided into 4 groups: defect group (empty bone defect, without application of LPT), graft group (bone defect filled with BioOss, without application of LPT), (defect+LPT) group (empty bone defect, with application of LPT), and (graft+LPT) group (bone defect filled with BioOss, with application of LPT). An OsseoPulse LED device (wavelength: 618 nm; output power: 20 mW/cm(2)) was initiated 24 hours postsurgery and performed every 24 hours for 7, 14, and 21 days. The LPT-applied and BioOss-filled defects presented a higher amount of new bone formation with trabeculae formation. These defects showed statistically significant lower values of inflammation severity, and fewer remnants of biomaterial were present. Within the limitations of this study, LPT has positive effects on bone healing histopathologically and histomorphometrically for the defects filled with BioOss 3 weeks after the rats' femora injury.
Keywords: Animals; Male; Rats; Rats, Wistar; Models, Theoretical; Low-Level Light Therapy; histopathology; Minerals; deproteinized bovine bone graft; histomorphometry; light-emitting diode; photobiomodulation